2008
DOI: 10.3357/asem.2071.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Interventions to Decompression Sickness in Rats: Comparison of Five Agents

Abstract: MONTCALM-SMITH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…In our study, there is no difference in DCS outcome and DCS severity between ASA pretreatment and control groups. This result corroborates previous studies in a rat model of DCS subjected to the same dose of 100 mg/kg three times daily for 2 days before hyperbaric exposure (18). However, only one study in a rat model of DCS has shown a significant decrease in DCS incidence (22% in ASA group vs. 40% in control group) and DCS severity (12% incidence of death in ASA group vs. 31% in control group) with ASA pretreatment before a hyperbaric exposure in a dry chamber and a fast decompression.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, there is no difference in DCS outcome and DCS severity between ASA pretreatment and control groups. This result corroborates previous studies in a rat model of DCS subjected to the same dose of 100 mg/kg three times daily for 2 days before hyperbaric exposure (18). However, only one study in a rat model of DCS has shown a significant decrease in DCS incidence (22% in ASA group vs. 40% in control group) and DCS severity (12% incidence of death in ASA group vs. 31% in control group) with ASA pretreatment before a hyperbaric exposure in a dry chamber and a fast decompression.…”
Section: Discussionsupporting
confidence: 94%
“…The experimental design is detailed in Figure 1. Previous studies showed that bubble formation and incidence of decompression sickness were highly dependent upon body weight of the rat [24], [25], [26]. Protocols using rats with a body weight above 350 g produced severe DCS with severe neurological symptoms and death.…”
Section: Methodsmentioning
confidence: 99%
“…Bubble formation in blood induces activate the vascular endothelium, stimulate prothrombotic phenomena and induce inflammation: platelet and leukocyte activation have been observed, associated with elevated production of cytokines and cell adhesion stimulators [2], [4], [5]. It is now accepted that severe DCS is a systemic pathophysiological process that may induce tissue reaction that promotes ischemic damage in the spinal cord or the brain [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, increased levels of proinflammatory circulating cytokines especially IL-6, TNF alpha and IFN gamma have been detected in animal models of DCS, correlated with the upregulated expression of selectins in the lungs and brain [4], [23]. It has been suggested that the activation of the body’s defense system initiates a vicious cycle that leads to multiple organ failure unless the DCS is adequately treated [8].…”
Section: Introductionmentioning
confidence: 99%